Photocatalytic Degradation of 4-Nitrophenol by C, N-TiO2: Degradation Efficiency vs. Embryonic Toxicity of the Resulting Compounds - Osin, Oluwatomiwa A.; Yu, Tianyu; Cai, Xiaoming; Jiang, Yue; Peng, Guotao; Cheng, Xiaomei; Li, Ruibin; Qin, Yao; Lin, Sijie (Frontiers in Chemistry, 2018)
The photocatalytic activity of TiO2 based photocatalysts can be improved by structural modification and elemental doping. In this study, through rational design, one type of carbon and nitrogen co-doped TiO2 (C, N-TiO2) photocatalyst with mesoporous structure was synthesized with improved photocatalytic activity in degrading 4-nitrophenol under simulated sunlight irradiation. The photocatalytic degradation efficiency of the C, N-TiO2 was much higher than the anatase TiO2 (A-TiO2) based on absorbance and HPLC analyses. Moreover, using zebrafish embryos, we showed that the intermediate degradation compounds generated by photocatalytic degradation of 4-nitrophenol had higher toxicity than the parent compound. A repeated degradation process was necessary to render complete degradation and non-toxicity to the zebrafish embryos. Our results demonstrated the importance of evaluating the photocatalytic degradation efficiency in conjunction with the toxicity assessment of the degradation compounds.